Metacognitive Strategy on Students’ Literal and Inferential Comprehension in L2 Reading - Ninda Oktaviana Putri; Entis Sutisna; Asih Wahyuni (FKIP UNIVERSITAS PAKUAN, 2021)
Reading is one skill that should be master by the students who want to learn English. However, students often find difficulties while learning English. To solve the problem, students should mastered four language English skills, and one of them is Reading. However, based on the preliminary data taken by the Researcher, it shows that students often did not know what they read. They are not aware of their own reading process. To solve this problem, the students need to know what kind of strategy that they should use while reading. The appropriate strategy that student should use when read is the metacognitive strategy. This paper entitled Metacognitive strategy on students’ literal and inferential comprehension is conducted to know what kind of metacognitive strategy used on students’ reading comprehension, especially their literal and inferential. The aims of this study are to know what kind of metacognitive strategy used on students’ literal and inferential comprehension skills in L2 reading and how are the use of metacognitive strategy on students’ literal and inferential comprehension to their reading skill. There were 3 strategy subscales or factors; Global Reading Strategies, Problem-Solving Strategies and Support Reading Strategies. Results revealed that participants reported frequent use the third metacognitive-strategy types stated by Mokhtari. K And Reichard. The method of this research is qualitative research. It takes place at Pakuan University. The population of this study were Fifth-semester students of the English language Education study program. While the sample of this research are students from class A and Class D that consists of 37 students. The technique and instruments of collecting data for this research are questionnaires, interviews, and forum group discussions. In conclusion, the result shows that the students use metacognitive strategy in their reading process.